Post‐Genome‐Wide Association Study Challenges for Lipid Traits: Describing Age as a Modifier of Gene‐Lipid Associations in the Population Architecture Using Genomics and Epidemiology (PAGE) Study. (28th June 2013) - Dumitrescu, Logan; Carty, Cara L.; Franceschini, Nora; Hindorff, Lucia A.; Cole, Shelley A.; Bůžková, Petra; Schumacher, Fredrick R.; Eaton, Charles B.; Goodloe, Robert J.; Duggan, David J.; Haessler, Jeff; Cochran, Barbara; et al.
Summary: Numerous common genetic variants that influence plasma high‐density lipoprotein cholesterol, low‐density lipoprotein cholesterol (LDL‐C), and triglyceride distributions have been identified via genome‐wide association studies (GWAS). However, whether or not these associations are age‐dependent has largely been overlooked. We conducted an association study and meta‐analysis in more than 22, 000 European Americans between 49 previously identified GWAS variants and the three lipid traits, stratified by age (males: <50 or ≥50 years of age; females: pre‐ or postmenopausal). For each variant, a test of heterogeneity was performed between the two age strata and significant Phet values were used as evidence of age‐specific genetic effects. We identified seven associations in females and eight in males that displayed suggestive heterogeneity by age (Phet < 0.05). The association between rs174547 ( FADS1) and LDL‐C in males displayed the most evidence for heterogeneity between age groups (Phet = 1.74E‐03, I 2 = 89.8), with a significant association in older males (P = 1.39E‐06) but not younger males (P = 0.99). However, none of the suggestive modifying effects survived adjustment for multiple testing, highlighting the challenges of identifying modifiers of modest SNP‐trait associations despite large sample sizes.